Pengembangan Sistem Informasi Manajemen Inventaris Berbasis Web Untuk Optimalisasi Operasional di PT. Indah Permata - Maria Erince Seuk; Rouli Doharma (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Inventory management is a crucial aspect of ensuring operational efficiency, especially in trade and distribution companies like PT. Indah Permata. The manual recording system currently in use creates several challenges, such as data entry errors, duplication, and delayed reporting. Therefore, this study aims to develop a web-based inventory management system to address these issues and optimize the company's operations. The development method used is the waterfall model, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The system was developed using PHP Native and MySQL as the database. The results show that the system improves operational efficiency by speeding up real-time item tracking, minimizing human errors, and enhancing data security and accessibility. With features such as login, data addition, editing, deletion, search, and export, the system enables administrators to manage inventory more effectively. Additionally, it supports quick and accurate decision-making processes. This system can serve as a solution for other companies facing similar challenges in inventory management.